2022
DOI: 10.1002/pbc.29721
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary embolism in pediatric and adolescent patients with COVID‐19 infection during the SARS‐CoV‐2 delta wave

Abstract: Coronavirus disease 2019 (COVID‐19) infection in children has been associated with thrombosis, though few cases of COVID‐associated pulmonary embolism (PE) have been described. We performed a retrospective review of the nine cases of COVID‐19‐associated PE during the B.1617.2 variant surge at Texas Children's Hospital. The patient cohort largely contained unvaccinated obese adolescents. All patients were critically ill with two requiring catheter‐directed thrombolysis in addition to anticoagulation. Eight of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…4 G to I) induced by the κ and δ variants, which was greatest in the κ variant. Together, these data indicate that the κ and δ variants induce stronger platelet activation, which is consistent with clinical reports of severe thrombosis in patients infected with these variants [ 11 , 63 , 64 ].…”
Section: Resultssupporting
confidence: 90%
“…4 G to I) induced by the κ and δ variants, which was greatest in the κ variant. Together, these data indicate that the κ and δ variants induce stronger platelet activation, which is consistent with clinical reports of severe thrombosis in patients infected with these variants [ 11 , 63 , 64 ].…”
Section: Resultssupporting
confidence: 90%
“…We read the publication on “Pulmonary embolism in pediatric and adolescent patients with COVID‐19 infection during the SARS‐CoV‐2 delta wave”. 1 Cohen et al. concluded that this report stresses the importance of maintaining a high index of suspicion for pulmonary embolism (PE) in pediatric COVID‐19 infection and vaccinating obese adolescent patients.…”
mentioning
confidence: 88%
“…concluded that this report stresses the importance of maintaining a high index of suspicion for pulmonary embolism (PE) in pediatric COVID‐19 infection and vaccinating obese adolescent patients. 1 The thrombohemostatic disorder is a possible clinical problem in patients with COVID‐19 and COVID‐19 vaccine recipients. Indeed, after COVID‐19 vaccination or COVID‐19 infection, there is increased blood viscosity that might present a risk for thrombohemostatic disorder.…”
mentioning
confidence: 99%
“…substantially increased rates of venous thromboembolism secondary to covid-19 disease. [32][33][34] In particular, earlier strains of the SARS-CoV-2 virus were associated with an increased rate of pulmonary embolism (>30%) in patients admitted to hospital. [35][36][37] Nonetheless, we found an increase in the incidence of definite or possible vaccine induced immune thrombocytopenia and thrombosis.…”
Section: Open Access Open Accessmentioning
confidence: 99%